DEGRO guidelines for the radiotherapy of non-malignant disorders : Part II: Painful degenerative skeletal disorders - Ott, Oliver J.; Niewald, Marcus; Weitmann, Hajo-Dirk; Jacob, Ingrid; Adamietz, Irenaeus A.; Schaefer, Ulrich; Keilholz, Ludwig; Heyd, Reinhard; Muecke, Ralph (Strahlentherapie und Onkologie, 2015)
The purpose of this article is to summarize the updated DEGRO consensus S2e guideline recommendations for the treatment of benign painful degenerative skeletal disorders with low-dose radiotherapy.This overview reports on the role of low-dose radiotherapy in the treatment of enthesiopathies (shoulder syndrome, trochanteric bursitis, plantar fasciitis, and elbow syndrome) and painful arthrosis (knee, hip, hand, and finger joints). The most relevant aspects of the DEGRO S2e Consensus Guideline Radiation Therapy of Benign Diseases 2014 regarding diagnostics, treatment decision, dose prescription as well as performance of radiotherapy and results are summarized.For all indications mentioned above, retrospective and some prospective analyses have shown remarkable effects in terms of pain relief. Nevertheless, the Level of Evidence (LoE) and the Grade of Recommendation (GR) vary: LoE 1b-4 and GR A-C.Low-dose radiotherapy for painful degenerative skeletal disorders is effective in the majority of the patients and therefore it may be a reasonable therapeutic alternative when simple and non-invasive methods have been used without persistent success. For all discussed entities, single fraction doses of 0.5-1.0 Gy and total doses of 3.0-6.0 Gy/series applied with 2-3 fractions per week are recommended.
EVALuna2:18205